Non-pharmacological Approaches to Apathy and Depression: A Scoping Review of Mild Cognitive Impairment and Dementia - Oba, Hikaru; Kobayashi, Ryota; Kawakatsu, Shinobu; Suzuki, Kyoko; Otani, Koichi; Ihara, Kazushige (Frontiers in Psychology, 2022)
Apathy and depression are frequently observed as behavioral and psychological symptoms of dementia, respectively, and are important for ensuring adequate care. This study aims to explore effective non-pharmacological interventions for apathy and depression with mild cognitive impairment (MCI) and dementia. Five search engines including PubMed, Scopus, CINAHL, PsycInfo, and Web of Science were used to extract relevant studies. Inclusion criteria were studies that involved participants who were diagnosed with MCI or dementia, included quantitative assessments of each symptom, and employed randomized controlled trials. Twenty studies were extracted, with interventions having been conducted in care facilities, the community, and hospitals. Participants in many studies had MCI or mild-to-moderate dementia but were not diagnosed with the subtypes of dementia. Few studies had set apathy and depression as the primary outcomes of non-pharmacological interventions. The findings suggested that emotional and stimulation-oriented approaches to apathy and depression would be useful for people with MCI or mild-to-moderate dementia. It would be helpful for therapists to assess the clinical features of the target symptoms for selecting suitable interventions. Additionally, increasing the number of randomized controlled trials focusing on apathy or depression as primary outcomes would offer a more definite conclusion for future systematic reviews.